Regalado Pinedo, A. (2021). Crimen a la media noche en el puerto de la Navidad, 1561. Mi biblioteca histórica Anabasis. 253 pp. - Del Palacio Montiel, Celia (Letras Históricas E-ISSN: 2448-8372, 2023)
Reseña de libro.